Prevalence of Prefrailty and Frailty Among Older Adults in Germany: A Systematic Review, Meta-Analysis and Meta-Regression - Hajek, André; Kretzler, Benedikt; König, Hans-Helmut (Frontiers in Medicine, 2022)
Background: Various studies have identified the prevalence of prefrailty and frailty among older adults in Germany. Nevertheless, there is no review systematically synthesizing these studies. Thus, our aim was to close this gap in knowledge. Moreover, another aim was to perform a meta-analysis to synthesize the pooled prevalence of prefrailty and frailty. A further aim was to explore potential sources of heterogeneity based on a meta-regression. Methods: Three electronic databases (PubMed, PsycINFO, CINAHL) were searched (plus an additional hand search). Observational studies determining the prevalence of frailty among older adults aged 65 years and over in Germany were included, whereas disease-specific samples were excluded. Data extraction included description of the sample, operationalization of frailty, statistical analysis, sample characteristics and main findings. The established Joanna Briggs Institute (JBI) standardized critical appraisal instrument for prevalence studies was used for evaluating the quality of the studies. Important steps were performed by two reviewers. Results: In sum, n=12 studies were included. Prevalence of frailty varied from about 2.4% to 25.6%. The pooled prevalence of frailty was 13.7% (95% CI: 9.0% to 18.5%). There was significant heterogeneity between studies (I²=98.9%, p<.001). The pooled prevalence of prefrailty was 40.2% (95% CI: 28.3% to 52.1%; I²=99.6%, p<.001). Some evidence of a publication bias exists. Meta-regressions showed that some of the heterogeneity was explained by the tool to quantify frailty and the average age of the respective sample. Conclusion: Particularly the high prevalence of prefrailty should be highlighted since it is important to prevent individuals in old age from developing to frail status. This knowledge is important for the German society as a whole and for relevant stakeholders.